Bioengineered Myocardium Derived from Induced Pluripotent Stem Cells Improves Cardiac Function and Attenuates Cardiac Remodeling Following Chronic Myocardial Infarction in Rats - Miki, Kenji (AlphaMed Press, 2012)
Cell-based therapies are promising strategies for myocardial repair following myocardial infarction. Induced pluripotent stem (iPS) cells have the potential to generate many cardiomyocytes, and they hold significant promise for the application of regenerative medicine to heart failure. Here, we developed cardiac tissue sheets, termed bioengineered myocardium (BM), from mouse iPS cells and measured cardiac performance following BM implantation in a rat chronic myocardial infarction model. Immunostaining analyses revealed that the α-actinin(+) cell population was isolated with more than 99% purity under specific culture conditions. To evaluate the contribution of BM to the improvements in cardiac performance, we induced myocardial infarction in 30 F344/NJcl-rnu/rnu rats by left anterior descending coronary ligation. The rats were randomly divided into two groups, 2 weeks after ligation: a BM implantation group (n = 15) and a sham group (n = 15). Echocardiography and catheter examination showed that the BM implantation significantly improved cardiac function and attenuated cardiac remodeling compared with the sham group. Histological analyses demonstrated that the implanted BM survived at the epicardial implantation site 4 weeks after implantation. The implanted BM survived and attenuated left ventricular remodeling in the rat chronic myocardial infarction model. Thus, BM derived from iPS cells might be a promising new treatment for heart failure.